A computer aided design methodology for die-casting dies : a case study - Khin Maung Myint; Bohez, Erik L.J.; Duflou, Joost R.; Pandey, Indra M.; The Royal Thai Government (Bangkok : Asian Institute of Technology, 1994)
Die casting is the most productive and lowest-cost manufacturing technique for numerous strategic industrial components, and die design and die making is a major portion of the die casting. The quality of die cast product and the economics of the process are critically influenced by the prevailing technological conditions. To assist the designing of dies for small and medium die shops, this study was conducted to develop a computer-aided design methodology that design engineers can use to design the die casting dies. In this study general design rnles are presented for various die casting alloys. A case study is carried out to present design methodology which will be useful for small and medium die shops. Combination of bottom-up and top-down approach is applied to design a die casting die for a water pump body. Flow analysis is carried out to determine the flow pattern in the runner sections. Thermal analysis is also carried out to determine location and size of cooling waterlines. Providing thermal control units with this design, the optimal casting condition can be achieved.
A thesis submitted m partial fulfilment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1994
Keywords: Computer-aided design